Pengembangan Aplikasi Edukasi Seksual untuk Remaja dengan Metode Kuis berbasis Progressive Web App - Alfonsus Avianto Chandrawan; Fais Al Huda; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Sexual education is still often considered taboo by most Indonesian people. A survey conducted by Durex Indonesia shows that 84 percent of Indonesian teenagers have not received sexual education. In fact, it is very essential for sex education to be taught to teenagers, especially when they are entering adolescence. A sexual education application named "Edusex" was developed in this study using the prototyping development method. This application provides learning materials as well as quizzes that can be done to help teenagers understand the material. Apart from that, there is also a discussion forum and personal consultation feature with psychologists. Teenagers can use these features to consult regarding sexual problems they are encountering. The type of developed application is a progressive web app that allows users to access the application using various types of devices and has several mobile app functionalities. There are four types of testing, namely functional testing, compatibility, usability, and application usage impact testing. In functional testing, the result obtained is 100% valid for all functional requirements. The result of compatibility testing shows that the website can be accessed on most browsers that are commonly used. The application has also been able to be used properly by the users based on the usability test. Based on the application usage impact test, the Edusex application has increased the users' sexual knowledge.